Avaliação conjunta do uso e ocupação do solo e qualidade da água na microbacia do arroio estrela, como indicadores de qualidade ambiental - Folletto, Flávio Aguiar (Universidade do Vale do Rio dos Sinos, 2013)
This study was conducted in the watershed of the stream Estrela, one of the streams tributaries more anthropogenic of the Taquari river. This analysis aimed to evaluate jointly use and land cover mapping using the classes and their relationship with water quality that arrives in Taquari river. The study aims to develop maps for use and occupation the soil and identify if there is increase of water pollution, with the arrival of the waters of the basin. For the classification of land cover seven classes were defined, being; Urban Areas, Bare Soil, Water (Water Resources), Temporary Crops, Fields Natives, Native Vegetation and Vegetation Exotic. To compose the remainder of the evaluation was based on data pertaining to water quality, existing and described in the literature. Were Images used LANDSAT 7, combined with other techniques geotechnological, remote sensing especially, to classify the uses of land. Other software for processing digital geographic data, integrated work tools. Based on the proposed methodology, it was possible to identify satisfactorily the use and occupation of land prevailing at this study site. Moreover, observed the influence of land use on water quality parameters. Despite seasonal variations in pollutant concentrations, the low quality of local water resources, denote a quality standard Class 3 in the region.
Keywords: Uso do solo; Qualidade da água; Geotecnologias; Land use; Water quality; Remote sensing